Early Loss of Optic Cup with Increased Intracranial Pressure. (3rd September 2018) - Horsburgh, John; Bativala, Rustom; Burdon, Michael; Shah, Peter
ABSTRACT: A 54-year-old woman developed increased intracranial pressure due to chronic dural venous sinus thrombosis in the absence of significant comorbidity. In the years preceding diagnosis, the patient underwent routine diabetic retinopathy screening; however, gradual loss of optic cup and disc swelling was only retrospectively noted after marked papilloedema was evident at an optometry visit. The patient made a full recovery once the diagnosis was established. This case is novel in the literature as routine photographs, taken for diabetic retinopathy screening, demonstrate the natural history of papilloedema before medical intervention. Interestingly, these images show that a traditionally "late" sign of papilloedema – loss of cup – can be the sentinel abnormality. This finding may have significant clinical implications and reinforces the need for clinicians to compare investigation results with historical patient data.